Entre dragas y trasmallos : minería mecanizada y cambios en las actividades de pesca en comunidades negras de la cuenca media del río Atrato, Chocó, Colombia (2017)
ABSTRACT: Since the Colony, Atrato River has allowed the settlement of its banks, has become the main means of communication, and has been the source of livelihood for the black communities. Currently, the fishing is a priority activity for these communities because their livelihood, food and trade is derived from this activity. However, the basin of Atrato is suffering environmental impacts, the reduction of volumes, sizes, and species of fish Based on the local knowledge of fishermen, this article attempts to reconstruct some of the key elements for undergoing both the ecological processes of the Atrato basin and the sociocultural dynamics of the black communities. It is argued that there is a relationship between the changes occurred in production-extraction systems and introduction of new techniques for capture and the impacts that these activities generate in the reduction of fish stocks.